2018
DOI: 10.2139/ssrn.3108554
|View full text |Cite
|
Sign up to set email alerts
|

Multigrading and Child Achievement

Abstract: We exploit Italian law DPR 81/2009, which determines class composition, as an instrument to identify the causal effect of grouping students of different grades into a single class (multigrading) on children cognitive achievement. This article focuses on 7-yearold students-those at the beginning of their formal education. Results suggest that attendance in multigrade classes versus single-grade classes increases students' performance on standardized tests by 15-20 percent of a standard deviation. The positive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 17 publications
4
13
0
Order By: Relevance
“…Our paper adds to two strands of literature. First, our findings are consistent with, and generalize beyond, the existing research on multi-grade classes that exploited that small population variations in sparsely populated areas of Norway (Leuven and Rønning 2014) and Italy (Checchi and De Paola 2018; Barbetta et al 2019) lead to the lumping together of grades in rural middle and elementary school respectively. We show that the benefits of exposure to older pupils by way of a multi-grade class, also accrue in urban settings where multi-grade classes are created by design and where school-starters are placed in multi-grade classes often for only one year at a time.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our paper adds to two strands of literature. First, our findings are consistent with, and generalize beyond, the existing research on multi-grade classes that exploited that small population variations in sparsely populated areas of Norway (Leuven and Rønning 2014) and Italy (Checchi and De Paola 2018; Barbetta et al 2019) lead to the lumping together of grades in rural middle and elementary school respectively. We show that the benefits of exposure to older pupils by way of a multi-grade class, also accrue in urban settings where multi-grade classes are created by design and where school-starters are placed in multi-grade classes often for only one year at a time.…”
Section: Discussionsupporting
confidence: 90%
“…About 28% of schools in the US use a mixed class setup and more than a third of primary school pupils in France attend multi-grade classes (Leuven and Rønning 2014). Yet, multi-grade classes have not been widely studied, with the notable exceptions of studies of rural areas of Norway (Leuven and Rønning 2014) and Italy (Checchi and De Paola 2018; Barbetta et al 2019) where cohorts are often so small that pooling several year-groups is done out of necessity. By contrast in Scotland, a constituent nation of the United Kingdom and the subject of our study, multi-grade classes are consciously created in virtually all primary schools.…”
Section: Introductionmentioning
confidence: 99%
“…Examining assessments at the end of P1 informed by online standardised tests (https://standardisedassessment.gov.scot/), they find that children who spend their first year of school with older peers score at a higher level, with 'larger and more pronounced peer effects for literacy than for numeracy ' (p. 29). Employing a similar research design within a comparable institutional context, where some children are assigned to composite classes, Barbetta et al (2019) find for 7-year-old Italian second-graders 'a positive multigrade effect for younger children in the class and some possible negative multigrade effects for older children' (p. 4), in terms of maths and language standardised test scores.…”
Section: Peer Birth Month/agementioning
confidence: 99%
“…Employing a similar research design within a comparable institutional context, where some children are assigned to composite classes, Barbetta et al . (2019) find for 7‐year‐old Italian second‐graders ‘a positive multigrade effect for younger children in the class and some possible negative multigrade effects for older children’ (p. 4), in terms of maths and language standardised test scores.…”
Section: Month Of Birth Effects and Children’s Agesmentioning
confidence: 99%
“…Berry, (2010), Cornish, (2010) as cited in Taole, M.J. (2017) defined it as the class room in which a teacher has to teach the students of different grades. Barbetta, G. P., Sorrenti, G., Turati, G.(2018) identified that multigrade teaching is not only practised in developing countries but also experienced in developed countries like 28% schools in United States, France 37%, Finland 70%, Netherland 53%, Italy 20%. This is another discussion either the multigrade classes are by choice or by need.…”
Section: Research Questionsmentioning
confidence: 99%